Ethnopolitical Stability in Ukrine: Challenges and Prospects of Overcoming Them (example of Chernivtsi Oblast, Ukraine) - Nechaieva-Yuriichuk, Nataliia (Wydawnictwo Uniwersytetu Rzeszowskiego, 2019)
The article is dedicated to the main challenges of ethnopolitical stability in Ukraine on the example of Chernivtsi oblast'
Keywords: Ethnic groups, stability, challenges, Revolution of Dignity, poll